Subjective Well-Being Among Students Experiencing Broken Home: Case Study in Islamic Modern Boarding School - Triyuliasari, Anisah; Ainunnisa, Hanifah (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Students with broken home family conditions do not close the possibility that they have high subjective well-being. It is because each individual has a different perspective of self-acceptance and a different view of happiness for himself. Each individual has factors that contribute to the subjective condition of his well-being. This study aims to identify and describe the subjective well-being of teenagers experiencing broken homes in Darul Hikmah Islamic Modern Boarding School. This study uses a qualitative evaluation with a case study method, the subjects in this study are single subjects teenagers, and daughters who are experiencing broken home. This is evident from the cognitive aspects, positive effects, and negative effects found by the researchers. Several factors also influence the subjective well-being of the subject, including internal factors including emotional intelligence, gratitude and patience, self-acceptance, religiousness, and forgiveness. There are also external factors including social support, relationships with parents, economic factors, quality of education, and school.